Reading people : how seeing the world through the lens of personality changes everything - Bogel, Anne, 1978- (Baker Books, a division of Baker Publishing Group, 2017)
If the viral personality quizzes strewn about our social media accounts are any indication, we are collectively obsessed with the idea of defining and knowing ourselves and our unique places in the world. But what we're finding is this: knowing which famous movie character you are is easy, but actually knowing yourself isn't as simple as just checking a few boxes on an online quiz. Backed by extensive research and illustrated with engaging stories, Reading People explains what make you uniquely you, what makes the people in your life uniquely them, and why it all matters. Popular blogger Anne Bogel makes it easy. In this fascinating book, she collects, explores, and explains the most popular personality frameworks, such as the Myers-Briggs Type Indicator, StrengthsFinder, Enneagram, and others. She shares the life-changing insights that can be gained from each, along with practical applications across all facets of life, including love and marriage, productivity, parenting, the workplace, and spiritual life. Want to revolutionize the way you live, love, work, and pray? Understanding personality is the first step!--COVER.